Optomechanical Processing of Silver Colloids: New Generation of Nanoparticle-Polymer Composites with Bactericidal Effect - Siegel, Jakub; Kaimlová, Markéta; Vyhnálková, Barbora; Trelin, Andrii; Lyutakov, Oleksiy; Slepička, Petr; Švorčík, Václav; Veselý, Martin; Vokatá, Barbora; Malinský, Petr; Šlouf, Miroslav; Hasal, Pavel; et al. (International journal of molecular sciences, 2020)
The properties of materials at the nanoscale open up new methodologies for engineering prospective materials usable in high-end applications. The preparation of composite materials with a high content of an active component on their surface is one of the current challenges of materials engineering. This concept significantly increases the efficiency of heterogeneous processes moderated by the active component, typically in biological applications, catalysis, or drug delivery. Here we introduce a general approach, based on laser-induced optomechanical processing of silver colloids, for the preparation of polymer surfaces highly enriched with silver nanoparticles (AgNPs). As a result, the AgNPs are firmly immobilized in a thin surface layer without the use of any other chemical mediators. We have shown that our approach is applicable to a broad spectrum of polymer foils, regardless of whether they absorb laser light or not. However, if the laser radiation is absorbed, it is possible to transform smooth surface morphology of the polymer into a roughened one with a higher specific surface area. Analyses of the release of silver from the polymer surface together with antibacterial tests suggested that these materials could be suitable candidates in the fight against nosocomial infections and could inhibit the formation of biofilms with a long-term effect.
Keywords: polymery; Surface Properties; Metal Nanoparticles; antibakteriální látky; světlo; Polymers; Anti-Bacterial Agents; kovové nanočástice; teoretické modely; Silver; povrchové vlastnosti; Microbial Sensitivity Tests; elektrochemie; Models, Theoretical; mikrobiální testy citlivosti; Light; Electrochemistry; stříbro